Exploration of the Reading of Surah Mu’awwidzatain at the Ashabul Yamin Lasi Tuo Pondok Pesantren: A Study of the Living Quran in the Context of Spiritual Development of Santri - Hidayah, Syarifatul; Febriyeni, Febriyeni (IDRIS Darulfunun Institute, 2024)
This research focuses on the practice of articulating the al-Falaq and an-Naas at Pondok Pesantren Ashhabul Yamin Lasi Tuo, which has become an essential part of the santri spiritual lives. The research employs a descriptive qualitative approach, collecting data through direct observation, in-depth interviews with the santri and the managers of the wirid activities, and related documentation. Key informants in this study provide insights into how these surahs are integrated into daily routines and how this practice is embraced and understood by the madrasah community. The findings of this research reveal that the articulation of the mu’awwidzatain surahs at Pondok Pesantren Ashhabul Yamin has a significant impact on the spiritual development of the santri. This practice not only offers protection from external disturbances but also serves as a tool for developing inner strength, peace of mind, and discipline in daily life. Santri engaged in this practice shows improvements in focus, tranquillity, and determination, all of which are the results of deep reflection on the teachings of these surahs. However, this study also identifies some challenges in the implementation of this tradition, particularly in maintaining its consistency and relevance amid social and environmental changes. The implications of these findings underscore the importance of understanding the role of religious rituals in shaping the spiritual identity of santri in madrasah. Traditions such as the articulation of the mu’awwidzatain surahs should not only be seen as part of the religious curriculum but also as a vital means of instilling deep moral and spiritual values. Therefore, it is crucial to preserve and develop this tradition while adapting it to the dynamics and challenges faced in the modern era.